Strategi Pemasaran Paket Ibadah Haji dan Umroh dalam Merekrut Jamaah di Kantor KBIH Kota Bogor - Anjani, Rizkha Amalia; Ibdalsyah, Ibdalsyah; Hakiem, Hilman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Hajj and Umrah are two significant religious rituals in Islam, holding profound spiritual and religious value for Muslims. Hajj is a mandatory pilgrimage to be performed once in a lifetime by those who are financially and physically capable, whereas Umrah can be undertaken at any time as an opportunity to draw closer to Allah SWT. This study aims to explore the meaning and importance of Hajj and Umrah in the lives of Muslims. The research methodology employed is qualitative, involving the collection and analysis of various relevant sources such as the Quran, Hadith, and other Islamic literature. The findings reveal that Hajj and Umrah provide several primary benefits, including purification from sins, enhancement of faith and piety, and strengthening of global Muslim unity. Moreover, these rituals have significant social, economic, and cultural impacts on Muslim communities worldwide. In the context of globalization and modern technology, the practice of Hajj and Umrah has undergone significant development, enabling millions of Muslims from diverse countries to perform these rituals more conveniently and efficiently. This research is expected to deepen understanding of the significance of Hajj and Umrah in contemporary Muslim life and contribute to enriching existing Islamic literature.